Profile of patients seen in the disciplines of Prosthesis Dental of a Clinic School of Dentistry (Research, Society and Development, 2020)
In view of the increase of the life expectancy and the increasingly frequent search for improvement in its quality, it is necessary to observe the constant changes in the profile of patients who need prosthetic rehabilitation. The objective of this work was to evaluate the profile of patients seen in the dental prosthesis disciplines, of the clinic-school in dentistry of the UFCG, Patos/PB. Being carried out an study observational, descriptive, through a retrospective analysis of 195 medical records of patients treated between the academic period 2013.1 to 2015.1. For reasons of exclusion, the final sample of the study was 131 medical records. Therefore, the following data were verified; the majority were female patients (72.5%); the general average age of the patients was 49.7 years, ranging from 20 to 85 years; the type of edentulism most found was the partial (77.1%); and as for the type of dental prosthesis, the most used was the PPR bimaxillary with 29.8%, followed by the PT bimaxillary and PPF. The results obtained allowed to conclude what the patients are in average adults of female partially edentulous, with regular oral hygiene, where the condition of the dental remnants was favorable for the rehabilitation treatment.